ANALISIS KONTRIBUSI SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH KOTA SABANG - Dira, Haris Maulana; Azhar, Azhar; Deli, Anwar; Romano, Romano; Manyamsari, Ira (Elastisitas : Jurnal Ekonomi Pembangunan, 2023)
This study aims to find out how much the contribution of the tourism sector is to Regional Original Income (PAD) and to know the trend of the development of tourism sector income in Sabang City. The type of data used in this study is secondary data. Data was collected using a method in the form of time series data from 2018-2022. The analytical method to determine the contribution size is used Proportional analysis and to determine development trends is used Trend analysis (time series). The results of the study show that income from the tourism sector has decreased and increased in the last 5 years, during the pandemic phase the tourism sector experienced a drastic decline then after the pandemic period ended income returned to a positive trend.